Type 3 resistant starch from Canna edulis modulates obesity and obesity-related low-grade systemic inflammation in mice by regulating gut microbiota composition and metabolism. Issue 23 (16th November 2021) - Wu, Jiahui; Qiu, Minyi; Zhang, Chi; Zhang, Caijuan; Wang, Nan; Zhao, Fangyuan; LV, Liqiao; Li, Junling; Lyu-Bu, A. G. A.; Wang, Ting; Zhao, Baosheng; You, Shaowei; et al.
Abstract : The beneficial effects of Ce-RS3 might derive from gut microbiota changes, which might improve obesity and metabolic inflammation by altering host-microbiota interactions with impacts on the metabolome. Abstract : Obesity is a most prevalent human health problem. Several studies showed that appropriate modulation of gut microbiota could help reshape the metabolic profile of obese individuals, thereby altering the development of obesity. A nutritional strategy for treating obesity includes prebiotics. Type 3 Resistant Starch from Canna edulis (Ce-RS3) is a dietary fiber that exerts potential effects on the intestinal microbial community; however, the metabolic landscape and anti-obesity mechanism remain unclear. In the present study, obese mice were treated with Ce-RS3, and 16S rRNA gene sequencing and metabolomics were used to measure changes in gut microbiota and fecal metabolic profiles, respectively. At the end of the treatment (13 weeks), we observed slow weight gain in the mice, and pathological damage and inflammation were substantially reduced. Ce-RS3 constructs a healthy gut microbiota structure and can enhance intestinal immunity and reduce metabolic inflammation. Ce-RS3 increased the diversity of gut microbiota with enrichment of Bifidobacterium and Roseburia . Ce-RS3 regulated the systemic metabolic dysbiosis in obese mice and adjusted 26 abnormal metabolites in amino acids and lipids metabolism, many of which are related to the microbiome. More importantly, we found that the anti-obesity effect of Ce-RS3 can be transferred by fecal transplantation. The beneficial effects of Ce-RS3 might derive from gut microbiota changes, which might improve obesity and metabolic inflammation by altering host-microbiota interactions with impacts on the metabolome. In conclusion, Ce-RS3 can be used as a prebiotic with potential value for the treatment of obesity.